2019
DOI: 10.3390/ijerph16142531
|View full text |Cite
|
Sign up to set email alerts
|

The Climate Change, Food Security and Human Health Nexus in Canada: A Framework to Protect Population Health

Abstract: Climate change impacts on the Canadian food system pose risks to human health. Little attention has been paid to the climate change, food security, and human health nexus, resulting in a number of knowledge gaps regarding food system components that are most vulnerable to climate change. The lack of understanding of key dynamics and possible future impacts challenges the ability of public health officials and partners in other sectors to prepare Canadians for future health risks. A series of literature reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Therefore, food safety challenges involve a preparation and understanding in an interdisciplinary context. Furthermore, the large implications of climate change on public health and food safety have complex consequences (Schnitter and Berry, 2019).…”
Section: Interdisciplinaritymentioning
confidence: 99%
“…Therefore, food safety challenges involve a preparation and understanding in an interdisciplinary context. Furthermore, the large implications of climate change on public health and food safety have complex consequences (Schnitter and Berry, 2019).…”
Section: Interdisciplinaritymentioning
confidence: 99%
“…Studies have shown many climate change effects on the Nigerian agribusiness value chain. The effect will vary with the location and components of the value chain [37]. This means that the result in northern Nigeria will be different from southern Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Global climate change is one of the biggest challenges which the world is facing, and the problem is the focus of the global community [ 1 ]. It is well-known that climate change threatens natural and human systems [ 2 ]. The 2020 report of the Lancet Countdown reported that climate suitability for the transmission of infectious diseases increased for dengue, malaria, and pathogenic Vibrio bacteria [ 3 ].…”
Section: Introductionmentioning
confidence: 99%